Chitosan ultilization in biocomposite adsorbent in Iron (Fe) removal from landfill leachate - Daud, Zawawi; Awang, Halizah; Ibrahim, Farah Nur Diyana; Ab Aziz, Nur Adila; Ridzuan, Mohd Baharudin; Ahmad, Zulkifli; Abubakar, Mahmoud Hijab; Tajarudin, Husnul Azan (International Journal of Integrated Engineering, 2019)
: Leachate are very high strength wastewaters that contain a variety of pollutants that pose a serious threat to the environment if appropriate control measure is ignored. Composite adsorbent is an emerging, interesting and attractive alternative to conventional adsorbents and having the ability to act as catalysts due to their high reactivity and excellent selectivity towards specific pollutant compounds. This study investigated the potential of biocomposite adsorbent made from a combination of chitosan, feldspar and zeolite (CFZ) for the treatment of Iron (Fe) from leachate wastewater. Leachate characterization and batch adsorption experiments was conducted to determine the optimum conditions for pH, dosage and contact time parameter in the removal of Fe. The result shows that the concentration of Fe was 15.82 which exceeded the recommended limit. The optimum conditions also occurred at pH 5 with 6 gram of biocomposite dosage and at 180 minutes contact time. The corresponding removal efficiency for Fe is 90% with 0.0127 mg/g uptake capacity